Metabolic changes in methomyl poisoned rats treated by vitamin E. (April 2018) - Weng, J; Cai, B; Chen, J; Chen, B; Wu, H; Wen, C; Sun, F; Hu, L; Chen, C; Wang, X; Wang, Z
In this study, we developed a serum and urine metabolomic method based on gas chromatography–mass spectrometry (GC-MS) combination with biomedical results to evaluate the effect of vitamin E treatment on methomyl poisoning rats. The rats were divided into three groups: the control group, methomyl poisoning group, and vitamin E treatment group. Partial least squares discriminate analysis (PLS-DA) showed that methomyl poisoning induced metabolic perturbations. Compared to the control group, based on the urinary metabolomics data, the level of ribitol, l -proline, xylitol, hydrocinnamic acid, 11-cis-octadecenoic acid, octadecanoic acid, and hexadecanoic acid of methomyl poisoning group increased, while the level of 2, 3, 4-trihydroxybutyric acid, ethanimidic acid, pantothenic acid, and retinoic acid decreased. Vitamin E pretreatment effectively normalized the levels of metabolites in rat urine in vitamin E treatment group. There was no significant difference in rat plasma metabolomic data after acute methomyl poisoning. The results indicate that metabolomic method based on GC-MS may be useful to elucidate the vitamin E treatment for methomyl poisoning.